Social success in personal success models of modern student youth - L.V. Rozhkova; V.A. Gladilina (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. Success in life of each person is different. It can be based on model of social success, broadcast in society or, in case of mismatch of value bases, it can be built on its own basis, based on personal preferences, attitudes and values. In any case, we can say that each individual chooses and implements his or her own model of success. The main objective of the study is to analyze dominant models of personal success among student youth and their relationship with models of social success. Materials and methods. The study of youth success is based on analysis of theoretical approaches to concept and models of success, data of polls VTsIOM, FOM, regional studies, as well as results of the authorʼs research among university students in Penza and Saratov (2024). Results. The main models of success presented in works of domestic researchers are analyzed, dominant models of life success in environment of student youth, self-assessments of students’ success and means of their achievement are presented. Conclusions. According to the research results, it was found that modern students are more inclined to mix of American and compromise models of success. The main components of life success for young people are family and material well-being; ideals of successful people for them are people from their environment. The main means of achieving success are goal setting and planning and education, and students are willing to take risks to realize their goals.